Soviet Utopia vs. systemic transformation: Development paths of mono-functional industrial towns in Georgia - Kaczmarek-Khubnaia, Julia (Rozwój Regionalny i Polityka Regionalna, 2024)
The article aims to compare the development paths of selected industrial mono-functional towns of Georgia, considering, in particular, the changes that occurred after the country regained independence. The spatial scope includes four monotowns of Georgia: Chiatura, Kaspi, Tkibuli and Rustavi. The time frame of the detailed analysis, based on population data, covers the period 1922–2021 (in examining the changes that occurred in Chiatura and Tkibuli, reference was also made to the period prior to Georgia’s incorporation into the Soviet Union). Based on the research conducted using the case study and desk research methods, the article presents the possible directions of development of the monotowns in Georgia, which were identified based on the assumptions of path dependency theory. In the detailed results, the characteristic features of the units were indicated, and their development paths were presented (both in the Soviet period and after 1991). The study was concluded by assigning the towns to the priorly extracted variants of the development paths after 1991 (variants A and B).